Acurácia dos indicadores clínicos de conforto prejudicado em crianças e adolescentes com câncer em tratamento quimioterápico - Leandro, Tania Alteniza (2015)
Difficulties in measurement of clinical indicators and in the identification of human responses are common in clinical practice. This fact is related to the l ack of familiarity of nurses with the classification systems. In addition, some clinical indicators present similarity with others. This is therefore, another confusing factor during the diagnostic reasoning process. In this way, studies on indicators accu racy of Nursing Diagnosis can help during the diagnostic reasoning, contributing to the determination and differentiation of human responses. Given these facts, the present research aims to evaluate the measures of accuracy of clinical indicators in nursin g diagnosis of Impaired Comfort in children and adolescents with cancer in chemotherapy treatment. Research on diagnostic accuracy, with cross - sectional design in a public children's hospital of Fortaleza (CE), during the months of September 2014 to Februa ry 2015. In this study, 192 children and adolescents were evaluated. For data collection, we used an instrument developed for the research. The information obtained from the evaluation was analyzed to determine the presence or absence of Impaired Comfort indicators, based on a previously established protocol. Data were analyzed for the whole sample and then divided into subsamples according to place of care, age and gender. Statistical analysis was carried out using IBM® SPSS® for Windows® version 21.0 and R software version 2.12.1 To verify the sensitivity and specificity of each indicator, the method of latent class analysis was used. The research was approved by two Research Ethic Committees. As a result of the data analysis of the entire sample, most children and adolescents participating in the research were male (53.1%), with average age of 11 years. Most patients were evaluated in the day hospital (55.2%) and 53.6% were children. Acute Lymphoblastic leukemia (33.9%) and Osteosarcoma (12%) were the m ost identified subtypes of cancer in the sample. The indicators with highest prevalence were: Report of perceived feeling of discomfort (83.3%), Report of lack of satisfaction with the situation (56.3%), Irritability (55.2%), Report of lack of feeling comf ortable with the situation (52.6%), Fear (51.0%) and Cry (50.5%). The analysis of the final latent class model for all indicators and for the overall sample, Anxiety, Inability to relax, Lamentation, Disturbed sleep pattern, Itching report and symptoms of distress showed significant specificity values. On the other hand, Irritability, Report of lack of satisfaction with the situation and Report of perceived feeling of discomfort showed high sensitivity values. Impaired Comfort was present in 29.01% of the t otal study sample. Based on the results obtained, it is believed that further study of the indicators of Impaired Comfort in children and adolescents with cancer can contribute for the assistance in Pediatric Oncology and familiarize nurses with the diagno sis analyzed. Furthermore, the results allowed us to recognize the need to perform specific nursing interventions so that the most identified indicators are accurate during the inference of this diagnosis in children and adolescents with ca ncer in chemothe rapy treatment